2019
DOI: 10.1097/mph.0000000000001605
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Pain Experienced by Children and Adolescents With Cancer at Home Following Discharge From the Hospital

Abstract: An exploratory study was conducted to examine quality of life and pain experienced by pediatric cancer patients at home following discharge. Physical, cognitive, social, and emotional aspects of quality of life were measured, and how these may be affected by age, gender, diagnosis, and pain status. We also characterized intensity, location, and quality of pain experienced. A sample of 33 patients participating in a larger study was selected based on having pain on day of discharge, and having completed the Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
12
0
4
Order By: Relevance
“…Only the pain item from the MSAS was included in the report. The pain data from the APPT were reported in another article (Duran et al, 2019). Only pediatric cancer patients were included, because the MSAS has been validated only in children and adolescents with cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Only the pain item from the MSAS was included in the report. The pain data from the APPT were reported in another article (Duran et al, 2019). Only pediatric cancer patients were included, because the MSAS has been validated only in children and adolescents with cancer.…”
Section: Methodsmentioning
confidence: 99%
“…We also found that children and adolescents with leukemia had higher HRQoL in all aspects of the DCGM-37measurement than those with sarcoma. Children with leukemia only receive chemotherapy, but children with sarcomas receive complex therapy, such as combined chemotherapy, radiotherapy, and surgery [ 26 ]. The latter group may therefore experience more side effects or complications [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants may have seen no point in using the app in the absence of pain. However, informing health professionals about the absence of pain is still clinically important and should represent the gold standard (Duran et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the underlying cause, many children and adolescents with cancer experience pain at home (Duran et al, 2019), which can undermine their ability to perform age-appropriate activities (Linder & Hooke, 2019). Pain can severely affect the quality of life of the entire family (Van Schoors et al, 2018), who is already distressed by a sense of loss and turmoil ever since the cancer diagnosis (Mu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%